Low-energy homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials

By forming a hydroxide sol coating on the graphite anode material of waste lithium-ion batteries and using electromagnetic induction heating and calcining technology, the problem of repairing graphite anode material of waste lithium-ion batteries in the prior art is solved, and low-energy-consuming homogenization repair and efficient regeneration are achieved.

CN119009234BActive Publication Date: 2025-04-04ZHEJIANG ZHONGCHUANG RESOURCE RECYCLING INNOVATION CENT CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411473308.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-04-04
Estimated Expiration
2044-10-22

AI Technical Summary

Technical Problem

The prior art is difficult to effectively repair the graphite negative electrode material of used lithium-ion batteries in a low-energy-environment environment, resulting in high cost of recycled graphite and difficulty in market circulation.

Method used

By mixing the graphite negative electrode material of the used lithium-ion battery with the metal salt solution, a hydroxide sol coating is formed, and electromagnetic induction heating and calcining is carried out under an inert atmosphere, the metal particles and graphite itself are used to generate heat, so that the homogenization and repair of the graphite material can be achieved.

Benefits of technology

It has achieved low energy consumption homogenization repair of the graphite anode material of used lithium-ion batteries, reduced the cost of recycled graphite, improved its electrochemical performance, and had wide applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119009234B_ABST
    Figure CN119009234B_ABST
Patent Text Reader

Abstract

The present invention provides a low-energy consumption homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrodes. The method is to highly uniformly compound the failed graphite negative electrode material of the lithium-ion battery with a metal hydroxide sol, and then perform electromagnetic heating calcination in an inert atmosphere, generate heat through the electromagnetic effect of metal particles and graphite itself, save energy and reduce consumption, and then the derived nano-scale metal catalyzes the growth of the graphite surface, finally achieving homogenization regeneration of the failed graphite negative electrode. The method is simple, efficient and widely applicable.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of repairing and regenerating graphite negative electrodes of waste lithium-ion batteries, and in particular to a low-energy-consumption homogenizing repairing and regenerating method for graphite negative electrodes of waste lithium-ion batteries. Background Art

[0002] The graphite negative electrode of lithium-ion batteries has shown the characteristics of high stability and low cost, and has become the main negative electrode material that cannot be replaced by the current lithium-ion battery system. At present, the graphite of lithium-ion batteries mainly comes from natural graphite and artificial graphite. Among them, natural graphite must go through the processes of "mining-ore dressing-smelting and purification-spheroidization-modification and quality improvement" to become a qualified graphite negative electrode material. Artificial graphite is synthesized by mixing-spheroidization-graphitization and other operations of high molecular organic matter such as asphalt and phenolic formaldehyde. Both have undergone the process of ultra-high temperature (2800℃) graphitization, resulting in a relatively high cost of battery graphite negative electrode. However, the graphite of retired lithium-ion batteries is difficult to be effectively treated at present, and more waste graphite is piled up. Because its surface contains more electrolyte and other substances, it inevitably pollutes the environment. In addition, most waste graphite enterprises directly calcine it as fuel, resulting in serious waste of graphite resources and serious emissions of carbon dioxide. Therefore, it is of great significance to carry out the direct repair and utilization of waste graphite.

[0003] At present, the repair and utilization of waste graphite is mainly carried out through high-temperature pyrolysis, which has high energy consumption, resulting in high costs for recycled graphite and difficulty in entering the market. The reason is that graphite materials have high thermal stability, and under low energy consumption conditions, the carbon ring structure is difficult to move effectively and self-assemble, so it is difficult to achieve efficient repair of graphite materials. In addition, due to the different degrees of failure of waste graphite from different sources, simple crystal phase restoration technology is difficult to achieve uniform properties of the entire graphite, resulting in unstable output of recycled graphite and difficulty in entering the market.

[0004] Chinese patent CN114890414B discloses a method for recycling graphite materials in waste batteries, comprising the following steps: (1) acid leaching the graphite materials in the waste batteries, followed by washing and drying; (2) immersing them in a metal salt solution and drying them; (3) immersing them in an alkaline solution, filtering them and drying them; (4) placing them in an organic carbon source solution for hydrothermal reaction to form a double-layer coated graphite material A; (5) sintering the above materials to form a double-layer coated graphite material B; and (6) acid washing the double-layer coated graphite material B to obtain a porous C-coated graphite material.

[0005] However, this technical solution has some disadvantages: in this technical solution, the substance formed by metal elements is regarded as energy storage active substance, and the metal ions deposited on the graphite surface are relatively small. Some metal ions will enter the liquid phase, resulting in incomplete coating of graphite materials, low coating content, and difficulty in achieving homogenization. In addition, the two-stage process causes high energy consumption of the material, which is not suitable for large-scale production.

[0006] In summary, in response to the above problems, developing low-energy restoration technology for waste graphite and technology that can achieve homogenized restoration of waste lithium-ion battery graphite negative electrode materials in a low-energy environment are very important for the high-value utilization of waste graphite resources and environmental protection. Summary of the invention

[0007] The purpose of the present invention is to provide a low-energy consumption homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials in view of the shortcomings of the prior art. The method is to highly uniformly compound the graphite negative electrode materials of the waste lithium-ion batteries with metal hydroxide sols, and then perform electromagnetic heating calcination in an inert atmosphere, generate heat through the electromagnetic effect of metal particles and graphite itself, save energy and reduce consumption, and then catalyze the growth of the derived nano-scale metal on the graphite surface, finally achieving high-value homogenization regeneration of the failed graphite negative electrode materials. The method is simple, efficient and widely applicable.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] A low-energy homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials comprises the following steps:

[0010] S1, uniformly dispersing the waste lithium-ion battery graphite negative electrode material in a metal salt solution and mixing them to obtain an aqueous solution;

[0011] S2, adding an alkaline solution to the obtained aqueous solution, using the alkaline solution to induce the metal ions to precipitate in situ into a gel on the surface of the spent graphite to form a hydroxide sol coating layer;

[0012] S3, washing and drying the hydroxide sol coating layer to obtain a precursor mixed material;

[0013] S4. The precursor mixed material is subjected to low-energy calcination by electromagnetic induction heating under an inert atmosphere to obtain homogenized regenerated graphite.

[0014] Preferably, the metal salt is at least one of soluble nickel-based and molybdenum-based metal salts, and the soluble nickel-based metal salt is at least one of nickel nitrate, nickel acetate and nickel sulfate.

[0015] A nickel-based metal salt solution is mixed with graphite, and the types of salts selected first are nickel, molybdenum and other elements; in addition, this scheme adopts an in-situ composite method, that is, by placing waste graphite in a metal salt solution, the formed hydroxide sol is in-situ composited with graphite, and the strong adsorption of the sol and the multi-defect adsorption characteristics of the waste graphite surface are utilized to achieve effective composite of the sol and the waste graphite. After composite, compared with existing products, the content of metal hydroxide is higher, which is conducive to the subsequent reduction catalytic effect.

[0016] Preferably, in S1, the concentration of the metal salt solution is 0.05 mol / L to 0.5 mol / L.

[0017] Preferably, in S2, the main component of the alkaline solution is at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide and ammonia water.

[0018] Preferably, in S2, the concentration of the alkaline solution is 0.1 mol / L, the dropping method is uniform dropping, and the dropping speed is 0.05-5.0 ml / min.

[0019] Preferably, in S4, the inert atmosphere is mainly one or more of argon, nitrogen, a hydrogen-argon mixture, and a hydrogen-nitrogen mixture.

[0020] Preferably, in S4, the magnetic field heating intensity of the electromagnetic induction heating is 2-10 mT, and the heating time is 1-5 h.

[0021] Also preferably, in S4, the calcination temperature is 1400°C.

[0022] It should be noted that the alkaline solution is further added to the nickel-based metal ion solution and the solid-liquid mixture of waste graphite, and then the hydroxide ions and metal ions are used to form hydroxide precipitation, and an in-situ composite method is adopted, that is, the waste graphite is placed in a metal salt solution, and the formed hydroxide sol is in-situ composited with the graphite, and the strong adsorption of the sol and the multi-defect adsorption characteristics of the waste graphite surface are utilized to achieve effective composite of the sol and the waste graphite. After composite, compared with existing products, the content of metal hydroxide is higher, which is conducive to the subsequent reduction catalytic effect.

[0023] The present invention does not require the addition of additional organic ligands, nor does it require the introduction of other carbon sources in subsequent experimental processes, so that the content of non-energy storage activated carbon in the graphite negative electrode material is low, the overall capacity is greatly improved, and the cost is greatly reduced, and it has the characteristics of low energy consumption and low cost.

[0024] The hydroxide sol coating layer is different from the metal hydroxide in the prior art. First, the content is different. The content in the prior art is relatively small, and its main function is to serve as an energy storage active substance. In addition, the form of existence is different. The metal hydroxide in the prior art exists in a scattered distribution, while the hydroxide gel in this scheme mainly exists in the form of large-scale coating.

[0025] The beneficial effects of the present invention are:

[0026] (1) The present invention uniformly disperses the spent graphite negative electrode material in an aqueous solution containing metal ions, and then directly adds an alkaline solution to the aqueous solution to induce the metal ions to form a hydroxide sol coating layer on the surface of the spent graphite negative electrode material by in-situ gelation. At the same time, by taking advantage of the unstable characteristics of the hydroxide sol, the rapid heating under low energy consumption makes the sol difficult to agglomerate and quickly decompose, metal oxides are derived. The defective carbon atoms on the surface interface of the spent graphite negative electrode material are highly active. The metal oxides react with the active carbon atoms, on the one hand, removing the highly active active carbon atoms and improving the initial coulombic efficiency of the regenerated graphite. On the other hand, the induced metal nanoparticles uniformly catalyze the homogenization repair of the graphite surface under low energy consumption, thereby improving the capacity of the regenerated graphite regeneration material.

[0027] (2) The present invention introduces the electromagnetic induction heating principle for the first time in the field of repair, calcining the precursor mixed material to induce magnetic resonance of graphite, metal ions and other substances, thereby achieving corresponding heating, and realizing the homogenized electromagnetic regeneration of the failed graphite negative electrode material of the waste lithium-ion battery, thus avoiding the problem of high energy consumption in traditional repair methods, and having the advantages of fast heating speed, high efficiency, low energy consumption, energy saving and environmental protection;

[0028] (3) The present invention achieves uniform dispersion of the metal hydroxide sol on the surface of the graphite material by directly adding an alkaline solution and a hydroxide sol to the mixed metal salt solution, thereby inducing the decomposition and reduction of the hydroxide to generate metal nanoparticles attached to the surface of the failed graphite, catalyzing the migration of carbon atoms on the surface of the graphite to complete the repair, and ultimately achieving the purpose of regenerating the failed graphite negative electrode material and improving the electrochemical performance.

[0029] In summary, the present invention has the advantages of simple operation, low energy consumption, good effect, high efficiency and wide applicability. The method can not only realize the homogenized repair of the graphite surface interface structure of the failed graphite negative electrode material under low energy consumption and achieve high-value homogenized regeneration, but also significantly improve the electrochemical performance of the graphite negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM electron microscope image of the hydroxide sol coating layer of the present invention;

[0031] Figure 2 This is the SEM electron microscope image of the regenerated graphite of the present invention;

[0032] Figure 3 This is a SEM electron microscope image of graphite from a waste lithium-ion battery of the present invention. DETAILED DESCRIPTION

[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.

[0035] Example 1

[0036] This embodiment provides a low-energy consumption homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials, comprising the following steps:

[0037] S1. Dispersing the waste lithium-ion battery graphite negative electrode material uniformly in a nickel nitrate solution with a concentration of 0.1 mol / L by forced dispersion and mixing through ultrasound and stirring to obtain an aqueous solution, wherein the solid-liquid ratio of the waste graphite negative electrode material to the metal salt solution is 1:6 g / ml;

[0038] S2, adding a sodium hydroxide solution with a concentration of 0.1 mol / L to the obtained aqueous solution, and continuing to stir and mix for 0.5 h to form a graphite negative electrode material with a hydroxide sol coating layer;

[0039] S3, washing and drying the graphite negative electrode material of the hydroxide sol coating layer to obtain a precursor mixed material;

[0040] S4. The precursor mixed material is subjected to electromagnetic induction heating to 1400° C. in argon gas for calcination to obtain homogenized regenerated graphite; and then subjected to screening, demagnetization and other operations to obtain a high-performance repaired regenerated graphite material.

[0041] It should be noted that the graphite negative electrode material of the waste lithium-ion battery used in this embodiment is in powder form, which can be obtained by precise or crushing and disassembling, or the negative electrode material black powder can be purchased on the market.

[0042] In the step S2, the sodium hydroxide solution is added dropwise at a uniform speed, and the dropping speed is 1.0 ml / min.

[0043] In S4, due to the rapidity of the temperature rise of the electromagnetic induction heating system, the electromagnetic heating time is the calcination time; wherein, the magnetic field heating intensity of the electromagnetic induction heating is 5mT, and the heating time is 2h.

[0044] It is worth noting that the present invention adopts electromagnetic induction heating to achieve induced metal atomic reduction resonance heating with low energy consumption. If the calcination time is too short, it is difficult for the atoms on the surface of the failed graphite to catalyze self-repair completely, resulting in failure of the homogenized regenerated graphite. If the calcination time is too long, the energy consumption is too high and the cost increases seriously. The present invention preferably adopts nickel element, mainly utilizing the catalytic effect of nickel element. At the same time, its purpose is to utilize nickel atoms to catalyze the free movement of carbon atoms near the defective structure on the graphite surface, thereby obtaining the repair of the surface interface structure.

[0045] Comparative Example 1:

[0046] A low-energy homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials, the specific steps of the method are as follows:

[0047] S1. The waste lithium-ion battery graphite negative electrode material is subjected to electromagnetic induction heating under argon conditions, wherein the magnetic field strength selected in S4 is 5 mT and the heating time is 2 h, thereby obtaining a preliminarily repaired and regenerated graphite material.

[0048] Comparative Example 2:

[0049] A low-energy homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials, the specific steps of the method are as follows:

[0050] S1. The waste lithium-ion battery graphite negative electrode material and the nickel nitrate solution with a concentration of 0.1 mol / L are uniformly mixed at a solid-liquid ratio of 1:6, and the mixture is forced to disperse and mix by ultrasound and stirring, and the material is filtered and dried;

[0051] S2. The obtained mixed material is subjected to electromagnetic induction heating under argon conditions with a magnetic field intensity of 5 mT and a heating time of 2 h. The obtained material is graphite recycled material.

[0052] Comparative Example 3:

[0053] A low-energy homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials, the specific steps of the method are as follows:

[0054] S1, adding a sodium hydroxide solution with a concentration of 0.1 ml / L to the graphite negative electrode material solution of the waste lithium ion battery, wherein the dropping speed of the sodium hydroxide solution is 1.0 mol / min, continuing to stir and mix for 0.5 h, and then filtering and drying;

[0055] S2. The obtained mixed material is subjected to electromagnetic induction heating under argon conditions with a magnetic field intensity of 5 mT and a heating time of 2 h. The obtained material is graphite recycled material.

[0056] Comparative Example 4:

[0057] A low-energy homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials, the specific steps of the method are as follows:

[0058] S1. Evenly mix the waste lithium-ion battery graphite negative electrode material and a nickel nitrate solution with a concentration of 0.1 mol / L at a solid-liquid ratio of 1:6, and forcefully disperse and mix by ultrasound and stirring to obtain an aqueous solution;

[0059] S2, adding a sodium hydroxide solution with a concentration of 0.1 ml / L to the obtained aqueous solution, wherein the dropping speed of the sodium hydroxide solution is 1.0 ml / min, and stirring and mixing is continued for 0.5 h to form a hydroxide sol coating layer;

[0060] S3, filtering and drying the hydroxide sol coating layer to obtain a precursor mixed material;

[0061] S4. The precursor mixed material is heated in a tubular furnace under argon gas conditions, with a heating rate of 10°C / min, a holding temperature of 1000°C, and a holding time of 6 hours. The obtained material is a graphite recycled material.

[0062] Comparative Example 5:

[0063] A low-energy homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials, the specific steps of the method are as follows:

[0064] S1. Evenly mix the waste lithium-ion battery graphite negative electrode material and a nickel nitrate solution with a concentration of 0.1 mol / L at a solid-liquid ratio of 1:6, and forcefully disperse and mix by ultrasound and stirring to obtain an aqueous solution;

[0065] S2, adding a 0.1 ml / L pyridine ethanol solution to the obtained aqueous solution, wherein the sodium hydroxide solution is added at a rate of 1.0 ml / min, and stirring and mixing is continued for 0.5 h to form a sol coating layer;

[0066] S3, filtering and drying the sol coating layer to obtain a precursor mixed material;

[0067] S4. The precursor mixed material is subjected to electromagnetic induction heating under argon conditions with a magnetic field intensity of 5 mT and a heating time of 2 h. The obtained material is a high-performance homogenized recycled material.

[0068] Comparative Example 6:

[0069] Referring to the second and third steps in the process flow of application number 202210738986.7 in the prior art, namely:

[0070] S1, immersing the dried graphite material in a nickel nitrate solution with a concentration of 0.1 mol / L, and then drying it;

[0071] S2. Immerse the graphite material dried in the above step in a sodium hydroxide solution with a concentration of 0.1 ml / L, take it out and dry it to obtain a metal hydroxide-coated graphite material.

[0072] Embodiment 2:

[0073] The nickel nitrate solution in S1 was replaced with nickel sulfate solution, and the remaining homogenization steps were the same as those in Control Example 6.

[0074] Embodiment 3:

[0075] The nickel nitrate solution in S1 was replaced with nickel acetate solution, and the remaining homogenization steps were the same as those in Control Example 6.

[0076] Embodiment 4:

[0077] The concentration of the nickel nitrate solution in S1 was replaced with 0.05 mol / L, and the remaining homogenization steps were the same as those in Control Example 6.

[0078] Embodiment 5:

[0079] The concentration of the nickel nitrate solution in S1 was replaced with 0.5 mol / L, and the remaining homogenization steps were the same as those in Control Example 6.

[0080] Embodiment 6:

[0081] The uniform mixing according to the solid-liquid ratio of 1:6 in S1 is replaced by uniform mixing according to the solid-liquid ratio of 1:5, and the remaining uniform steps are the same as those in Control Example 6.

[0082] Embodiment 7:

[0083] The uniform mixing according to the solid-liquid ratio of 1:6 in S1 is replaced by uniform mixing according to the solid-liquid ratio of 1:10, and the remaining uniform steps are the same as those in the uniform control example 6.

[0084] Embodiment 8:

[0085] The sodium hydroxide solution in S2 was replaced with potassium hydroxide solution, and the remaining homogenization steps were the same as those in Control Example 6.

[0086] Embodiment 9:

[0087] The dropping speed of the sodium hydroxide solution in S2 is replaced with 0.5 ml / min, and the remaining homogenization steps are the same as those in Control Example 6.

[0088] Embodiment 10:

[0089] The dropping speed of the sodium hydroxide solution in S2 is replaced with 5 ml / min, and the remaining homogenization steps are the same as those in Control Example 6.

[0090] Embodiment 11:

[0091] The argon condition in S4 was replaced with nitrogen condition, and the remaining homogenization steps were the same as those in Control Example 6.

[0092] Embodiment 12:

[0093] The magnetic field strength in S4 was replaced with 2 mT, and the remaining uniformization steps were the same as those in uniformity control example 6.

[0094] Embodiment 13:

[0095] The magnetic field strength in S4 was replaced with 10 mT, and the remaining uniformization steps were the same as those in uniformity control example 6.

[0096] Embodiment 14:

[0097] The heating time in S4 was replaced with 1 h, and the remaining homogenization steps were the same as those in Control Example 6.

[0098] Embodiment 15:

[0099] The heating time in S4 was replaced with 5 h, and the remaining homogenization steps were the same as those in Control Example 6.

[0100] Performance Test:

[0101] The waste lithium-ion battery graphite negative electrode material in the above embodiments and comparative examples is the battery negative electrode black powder obtained on the market, and the three materials of recycled graphite material, acetylene black and sodium hydroxymethyl cellulose (CMC) are added with a certain amount of deionized water in a mass ratio of 8:1:1 to prepare a uniform slurry, and the obtained slurry is coated on a copper foil, and then placed in a vacuum oven at 100°C for 12 hours for drying, and the obtained pole piece is cut by a slicer into small discs with a diameter of 1.0 cm to become the obtained negative electrode material, wherein the copper foil surface is loaded with more than 1.0 mg of active substance.

[0102] The obtained negative electrode sheet, electrolyte, lithium sheet, battery shell, diaphragm, etc. are placed in an argon glove box for battery assembly. After sealing, the obtained battery is an assembled button battery.

[0103] After the button cell was left to stand for 12 h, it was placed on the blue-electric test channel for electrochemical performance testing, where the current density was set to 0.02 A / g, the voltage range was set to 0.01V~2.0V, and the test cycle was 100 cycles. The data obtained are the data directly displayed on the blue-electric tester, which can be directly used. The test results are shown in Table 1.

[0104] Table 1

[0105]

[0106] From Table 1, we can see that:

[0107] The test results of Comparative Examples 1-6 show that the addition of metal-based catalysts can effectively improve the degree of material repair and significantly increase the capacity of the regenerated material. In addition, the introduction of the electromagnetic heating system is conducive to the rapid heating of the material, so that the derived metal nanoparticles can effectively catalyze the regeneration of spent graphite. Through the synergistic effect of the metal-based catalyst and the electromagnetic induction heating system, efficient regeneration of spent graphite is achieved in a low-energy consumption environment.

[0108] By comparing the test results of Example 1 with those of Examples 4 and 5, it can be found that if the concentration of the metal salt solution is too high, the generated sol will be over-aggregated, causing the hydroxide sol to agglomerate on its own, and eventually causing the generated hydroxide sol and graphite to separate into two phases, making it difficult to coat the surface of the waste graphite and difficult to achieve the purpose of catalysis in the subsequent process; when the concentration of the solution is too low or too high, the metal gel polymerized on the surface is too little and difficult to coat completely, resulting in poor catalytic effect. On the other hand, it will also lead to excessive waste liquid, high post-processing costs, and serious waste of resources.

[0109] By comparing the test results of Example 1 with those of Examples 9 and 10, it can be found that if the dropping acceleration is too fast, the hydroxide gel will self-agglomerate severely and it will be difficult to evenly coat the surface of the waste graphite; if the dropping acceleration is too slow, the hydroxide sol will not be completely coated and the catalytic effect will not be significant.

[0110] By comparing the test results of Example 1 with those of Examples 12 and 13, it can be found that when the magnetic field strength is too small, the material is not heated completely, the hydroxide is difficult to decompose, and the derived metal nanoparticles are difficult to play an effective catalytic role; when the magnetic field strength is too large, the regenerated metal nanoparticles melt, causing the metal to melt and agglomerate, and the catalytic activity is lost.

[0111] By comparing the test results of Example 1 with those of Examples 6 and 7, it can be found that when the solid-liquid ratio is too small, it is difficult for the waste graphite to be well dispersed in the solution, and the self-agglomeration of the graphite particles in the aqueous solution is more serious, making it difficult to achieve effective coating of the hydroxide sol; when the liquid-solid ratio is too large, it is difficult for the waste graphite to form effective contact with the sol particles, ultimately leading to failure of the surface coating of the waste graphite.

[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A low-energy homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials, characterized in that: The following steps are involved: S1, uniformly mixing the graphite negative electrode material of the waste lithium-ion battery with the metal salt solution to obtain an aqueous solution; S2, adding an alkaline solution to the aqueous solution to induce the metal ions to precipitate in situ into a gel on the surface of the graphite negative electrode material to form a graphite negative electrode material with a hydroxide sol coating layer; S3, washing and drying the graphite negative electrode material of the hydroxide sol coating layer to obtain a precursor mixed material; S4, calcining the above-mentioned precursor mixed material by electromagnetic induction heating under an inert atmosphere to obtain homogenized regenerated graphite; In S1, the solid-liquid ratio of the graphite negative electrode material of the waste lithium-ion battery to the metal salt solution is 1:5-1:10 g / ml; In S1, the concentration of the metal salt solution is 0.05-0.5 mol / L; In S2, the alkaline solution is added dropwise at a uniform speed, and the dropwise addition speed is 0.05-5.0 ml / min; In S4, the magnetic field heating intensity of electromagnetic induction heating is 2-10 mT, and the heating time is 1-5 h; In the S1, the metal salt is a soluble nickel-based metal salt.

2. The low-energy homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials according to claim 1, characterized in that: The soluble nickel-based metal salt is at least one of nickel nitrate, nickel acetate and nickel sulfate.

3. The low-energy homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials according to claim 1, characterized in that: In S2, the main component of the alkaline solution is at least one of lithium hydroxide, sodium hydroxide, potassium hydroxide and ammonia water.

4. The low-energy homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials according to claim 1, characterized in that: In the S2, the concentration of the alkaline solution is 0.1 mol / L.

5. The low-energy homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials according to claim 1, characterized in that: In S4, the inert atmosphere is mainly one or more of argon, nitrogen, hydrogen-argon mixed gas, and hydrogen-nitrogen mixed gas.

6. The low-energy homogenization repair and regeneration method for waste lithium-ion battery graphite negative electrode materials according to claim 1, characterized in that: In the step S4, the calcination temperature is 1400°C.

Citation Information

Patent Citations

  • A method for recycling graphite materials from waste batteries

    CN114890414B

  • High-valued regeneration method for graphite negative electrode material of waste lithium ion battery

    CN117954725A

  • Recycled graphite for lithium ion batteries

    CN118554049A